Long-term Cognitive Outcomes and Socioprofessional Attainment in People With Multiple Sclerosis With Childhood Onset. (19th April 2022) - Portaccio, Emilio; Bellinvia, Angelo; Razzolini, Lorenzo; Pastò, Luisa; Goretti, Benedetta; Niccolai, Claudia; Fonderico, Mattia; Zaffaroni, Mauro; Pippolo, Lorena; Moiola, Lucia; Falautano, Monica; Celico, Claudia; et al.
Abstract : Background and Objectives: Patients with pediatric-onset multiple sclerosis (MS) can be especially vulnerable to cognitive impairment (CI) due to the onset of MS during a critical period for CNS development and maturation. The objective of this longitudinal study was to assess long-term cognitive functioning and socioprofessional attainment in the Italian pediatric MS cohort, previously assessed at baseline and 2 and 5 years. Methods: The 48 patients evaluated at the 5-year assessment were screened for inclusion. All participants were assessed with a cognitive test battery exploring 4 different cognitive abilities. Depression, fatigue, and socioprofessional attainment were also assessed. Mean cognitive z scores were calculated for the whole cohort, and their evolution over time was analyzed with an analysis of variance for repeated measurements test. Predictors of cognitive worsening or improvement were assessed with a linear mixed-model analysis. Results: Thirty-three participants were included (mean follow-up 12.8 ± 0.8 years). The global cognitive performance worsened at year 2 and improved at year 5, although the z score remained significantly lower than at baseline (−0.9 ± 1.2 vs −0.3 ± 0.9, p = 0.002). There was no significant variation between years 5 and 12 (−0.7 ± 1.1, p = 0.452). Higher IQ (>90) at baseline (effect 0.3, 95% CI 0.1–0.5, p = 0.017) and lower number of relapses in the 2 years before baseline (effect −0.1, 95% CI −0.1 to 0.1, p = 0.025) predicted better cognitive performances. Eighteen (54.5%) patients failed at least 2 tests compared with healthy controls and were defined as cognitively impaired. The presence of CI predicted worse socioprofessional attainment (β = 4.8, 95% CI 1.4–8.2, p = 0.008). Discussion: The longitudinal cognitive trajectory in pediatric-onset MS has a heterogeneous course over time, with a decline in the first years followed by a partial recovery over the long term. However, at the last follow-up evaluation, the proportion of impaired patients was more than double compared with baseline, with a negative impact on the individual's socioprofessional attainment in adulthood. This study underscores how cognitive reserve may partially mitigate the negative effects of brain damage, highlighting the critical importance of intellectual enrichment early during the disease course.